A Comparative Study of Game-Based Learning and Collaborative Learning in Computer Programming: Impact on Motivation to Learn, Programming Skills, and Learning Achievement - Daungcharone, Kannika; Thongkoo, Krittawaya (Journal of Applied Informatics and Technology, 2026)
This study explores the effects of game-based learning and collaborative learning on students’ motivation, programming skills, and learning achievement in computer programming. Participants included 198 first-year university students, divided into game-based learning environment (GBL-83 students) and collaborative learning environment (COL-115 students) groups. Four tools were utilised: pre-test, post-test, rubric scoring, and a motivation questionnaire. Results show that COL students exhibit significantly higher motivation across intrinsic, grade, self-determination, and self-efficacy dimensions. In programming skills, COL students excelled in identifying outputs, while GBL students demonstrated stronger abilities in identifying inputs and processes. No statistically significant difference in overall learning achievement was observed between the two groups. These findings underscore the advantages of collaborative learning in enhancing engagement and comprehension via teamwork and peer interaction, whereas game-based learning provides an interactive and enjoyable method for cultivating technical skills. Consequently, teachers ought to choose an appropriate pedagogical method and tools for their disciplines and learners.